Respuesta :

Answer: [tex]-11\sqrt{7}[/tex]

Step-by-step explanation:

To find the expression equal to the given, we will simplify the original.

   Given:

[tex]\displaystyle 2\sqrt{28} -5\sqrt{63}[/tex]

   Simplify:

[tex]-11\sqrt{7}[/tex]

           Answer:  [tex]-11\sqrt{7}[/tex]

ss062

Answer:  [tex]-11\sqrt{7}[/tex]

Step-by-step explanation:

[tex]2\sqrt{28}-5\sqrt{63}[/tex]

= [tex]2\sqrt{4*7}-5\sqrt{7*9}[/tex]

= [tex]2*\sqrt{4}*\sqrt{7} - 5*\sqrt{7} *\sqrt{9}[/tex]

= [tex]2*2*\sqrt{7} - 5*\sqrt{7}*3[/tex]

= [tex]4\sqrt{7} - 15\sqrt{7}[/tex]

= [tex]-11\sqrt{7}[/tex]